Consistent Modeling of Heterogeneous Lexical Structures - Laurent Romary (OpenEdition, 2012)
Our paper outlines a proposal for the consistent modeling of heterogeneous lexical structures in semasiological dictionaries, based on the element structures described in detail in chapter 9 (Dictionaries) of the TEI Guidelines. The core of our proposal describes a system of relatively autonomous lexical “crystals” that can, within the constraints of the relevant element’s definition, be combined to form complex structures for the description of morphological form, grammatical information, etymology, word-formation, and meaning for a lexical structure. The encoding structures we suggest guarantee sustainability and support re-usability and interoperability of data. This paper presents case studies of encoding dictionary entries in order to illustrate our concepts and test their usability. We comment on encoding issues involving <entry>, , <etym>, and on refinements to the internal content of <sense>.